The Influence of Guided Inquiry, Discovery Learning Models and Learning Styles on Learning Outcomes - Sri Endang Lestari; Hasruddin Hasruddin; Zulkifli Matondang (RIRAI Publisher, 2023)
This study was conducted with three objectives, namely: 1) to determine the difference in the influence of guided inquiry learning model and discovery model on student’s learning outcomes in science subjects on the human excretory system in class VIII of SMP Negeri 1 Kualuh Selatan ; 2) to determine the difference in the influence of visual, auditory, and kinesthetic learning styles on student’s learning outcomes in science subjects on the human excretory system in class VIII of SMP Negeri 1 Kualuh Selatan ; and 3) to determine the interaction between the two learning models and learning styles in influencing student’s learning outcomes in science subjects on the human excretory system in class VIII of SMP Negeri 1 Kualuh Selatan. The approach used in this study was a quantitative approach with a nonequivalent pretest-posttest group design with a 2x3 factorial treatment level. The research sample consisted of all students in class VIII1, totaling 28 students, and class VIII4, totaling 30 students, with the sampling technique using Cluster Random Sampling. The results of the study indicate that, firstly, students who were taught using the guided inquiry learning model performed better or excelled compared to students taught using the discovery learning model. Secondly, students who were taught using the visual learning style performed better or excelled compared to students taught using the auditory or kinesthetic learning styles. Thirdly, there is an interaction between the two learning models and learning styles on students' learning outcomes in science subjects on the human excretory system.